Distinct dietary patterns lead to lower B12 intake in type 2 diabetes: a case-control study - Rawat, Swapnil; Kumari, Meena; Nagpal, Jitender (International Journal of Public Health Science (IJPHS), 2024)
B12 deficiency has a higher prevalence in type 2 diabetes mellitus (T2DM) patients. The causes of this observation are poorly understood. Self-imposed (vegan/vegetarian) or advised dietary modification or intake of metformin could be contributing. Hence, we undertook this study to evaluate the dietary intake of Vitamin B12 in diabetes patients in comparison with age-matched healthy controls. Fifty T2DM patients (cases) and 50 age-matched volunteers (controls) aged 35-60 years were enrolled at a tertiary hospital, in New Delhi. Sociodemographic and dietary information was gathered and the average dietary intake of B12 was estimated using the Cobalamin Intake in North Indians-Food Frequency Questionnaire (COIN-FFQ) (developed and validated). Medical records were reviewed for biochemical parameters (HbA1c, lipid profile, and blood sugar) of the last three months. The mean age was 50.66±6.09 years (n=100) and the mean body mass index of 28.49±4.53 kg/m2. The mean intake of dietary B12 was 3.2±1.7 μg/day and 3.8±1.4 μg/day (p=0.047) in diabetes patients and controls respectively. Thirty-six percent of diabetes patients did not meet the currently recommended daily dietary intake of B12 intake (vs. 14% of controls; p=0.011). Diabetes patients have a lower dietary intake of Vitamin B12 attributable to their distinctive dietary pattern. It is necessary to explore the factors leading to lower dietary B12 intake in diabetes patients.